Tykociński przytułek wojskowy w XVII w. – funkcje społeczne i militarne - Sierba, Michał (Acta Universitatis Lodziensis. Folia Historica, 2015)
The article describes seventeenth century history of one of the buildings in Tykocin – alumnat. It is the traditional name of an old almshouse for veterans, which was founded by Christopher Wiesiołowski in year 1633. It is a four-wing building with an internal courtyard. In the southeastern corner of the alumnat there is a half-round apse. Two towers were the defensive advantage of the building. In the 17th century the alumnat held several functions. It was founded as a charitable institution for 12 noble war veterans, who were wounded defending Polish-Lithuanian Commonwealth, or were unable to earn for living due to their old age. Because of its defensive qualities and being located in the nearness of the bridge on the Narew River, the alumnat was used as one of defending points during Polish-Swedish war, called “the flood”. At that time the alumnat was obstructing access to the Tykocin fortress. After the war the alumnat became a temporary shelter not only for veterans, but also for people who had lost their homes during the war. In alumnatic apse there was a Roman Catholic chapel. In year 1660 the Tykocin’s church was destroyed in a fire. After this incident the chapel in alumnat was used as a temporary church for Tykocin’s community.